Influence of Promotion, Product Quality and Brand Regarding POCO Product Purchasing Decisions (Case Study of the Xiaomi Official Store Indonesia Online Store).: Pengaruh Promosi, Kualitas Produk dan Merek Terhadap Keputusan Pembelian Produk POCO (Studi Kasus Pada Toko Online Xiaomi Official Store Indonesia). - Yudha Kesuma, Muhammad; Susetyo, Bagus; Naufal Batubara, Muhammad (UPMI Proceeding Series, 2024)
The research was directed entirely to determine the impact of Promotion, Product Quality, and Brand with the method of partial hypothesis and simultaneous hypotheses on the Purchase Decision of the POCO smartphone product in the online store Xiaomi Official Store ID. The study used 100 respondents with the technique of the Random Sampling method. The method applied in this research is primary data starting from the questionnaire. This research shows that the Promotion affects the Purchase Decision of the POCO product in the Xiaomi Official Store ID online store. The quality of the product influences the Purchasing Decision for POCO products at the Xiaomi official store ID online shop. Markers influence the purchase decision of POCOs products in the online store of the Xiaomi official store ID. There is an enormous influence between Promotion, Product Quality and Brand on the decision to purchase POCO products in Xiaomi official shop ID online.